FEATURES OF SMALL BUSINESS LENDING IN FOREIGN COUNTRIES - Харабара, Віолетта; Грешко, Роман Ігорович; Третякова, Олена Василівна (. Kharabara Violetta, Greshko Roman, Tretyakova Olena. Features of small business lending in foreign countries. The X th International scientific and practical conference «Trends in the development of modern scientific thought» November 23-26, 2020 Vancouver, Canada.Pp.74-77., 2020)
The article examines current trends in economically developed countries regarding state support of entities small business. The activity of state institutions on advisory, informational and financial assistance to small businesses. The availability of preferential credit programs is considered for small business.
Keywords: business; banking market